MODEL PERANGKAT LUNAK MONITORING DAN EVALUASI IMPLEMENTASI STANDAR MUTU JALAN DAERAH - Taufik Mulyono, Agus; Santosa, Wimpy; Budi Suparma, Latif (Jurnal Transportasi, 2012)
One of the root problems causing early damages on provincial and district roads is road administratorsâ and developersâ low compliance against the road standards. To deal with this issue, a systemic logic model has been developed to facilitate the monitoring and the evaluation analyses of road standards implementation. The model was written in Java Runtime Environment version 6 and designed to feature portability, acceptability, applicability, and useability. The model was developed based on expert survey and typology analysis to gather and select the determining variables and their indicators.Model application in the case of SNI 03-2853-1992(guidelines on constructing road foundation using crushed stones) implementation is demonstrated in this paper.The results showed 58.50% of the sample âownâ the standard, 61.18% âunderstandâ the standard, 60.52% âimplementâ the standard, 51.39% âoverseeâ the implementation of the standard, and therefore the overall implementation score for the said standard was 59.08%. The model developed in this study has the potentials to provide recommendations to road administrators on whether or not a standard needs revision or even abolition.Keywords: evaluation, monitoring, quality standard, provincial and local roads